Health Information Science and its growing popularities in Indian self financed universities: Emphasizing Private Universities—A Study - Paul, P.K.; Aithal, P.S.; Bhuimali, A. (International Journal of Scientific Research in Biological Sciences, 2018)
Health is a major concern of today’s age. The development of information technology and computing changes the entire arena of life and the gradual development became responsible for the emergence of Digital Society. Information Technology is about the collection, selection, organization, processing, management and dissemination of information and similar contents viz. data and knowledge. For this task and affairs, several information technological tools have been used and it is increasing rapidly. Today it is very difficult to find out an area where utilization of information technology is absence. Hence healthcare is not an exception. Digital Health becomes an important concept these days for the creation of digital health and medical contents. Similar to other areas like Digital Business, Digital Marketing, Digital Education, Digital Health become a concept and key strategy for the development and modernization of healthcare affairs powered by Information Science and Technology. The integration and combination of information technology and computing create a separate domain and branch called ‘Health Information Science’. However, it is important to note that it is also known as Health Informatics nomenclature in the line of UK based academic units. Initially, the branch was mainly popular in the western countries and developed countries but gradually it is rising as a branch of study in a country like India. Private universities in India are rapidly increasing and the growth, initiative of private initiative is noticeable. This paper is conceptual in nature and deals with aspects of Health Informatics including its growing trends as a program of study in private universities in India.